Environmental Restoration of Metal-Contaminated Soils - Chiampo, Fulvia; Zacchini, Massimo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue entitled "Environmental Restoration of Metal-Contaminated Soils" focuses on the issues linked to soils contaminated with heavy metals and metalloids, dealing with current research activities around the world at the laboratory and field scale. These activities are the pillars for the application of strategies on a real-world scale, to remediate industrial soils affected by the problem. When an industrial soil contains pollutants, the main problem is the removal of these compounds. However, other features are present, linked to the health of the population living in its proximity. This Special Issue reports experimental run findings with the aim of removing heavy metals and/or metalloids from soil, making use of challenging techniques, and also demonstrating approaches for the assessment of the risks to human health.